Small tractors in the developing world - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Small four-wheeled tractors for the Tropics and sub-Tropics: their role in agricultural and industrial development, Rudolf Holtkamp GTZ Weikersheim, Margraf 1990 248pp, ISBN 3 8236 11615 ISSN 0932 3074 GTZ, D-6236 Eschborn, GERMANY